Análise do cenário global político-econômico do setor de energias renováveis com foco nas fontes solar fotovoltaica e eólica (2010 - 2016) - Parente, Patrícia Asfor (2018)
In recent years, renewable energies have gained a greater emphasis on the world energy matrix. This expansion is taking place in a scenario where discussions associated with the global warming are increasing. Thus, this study aims to contextualize the expansion of new renewable energies in the global scenario between the years 2010 and 2016, as well as the prospects of cost reduction for solar photovoltaic and wind technologies. For this, it was carried out a bibliographical review and data collection to understand the best practices of incentive to the renewable energies applied in the world. In this analysis, the implementation of support policies for new renewable energy sources becomes essential so that they can meet the growing energy demands of the societies. However, these support mechanisms are subject to the changes and weaknesses of the economic markets. Due to these vulnerabilities, between 2010 and 2016, investments in renewable energies had great variations that were caused by both the political instabilities and the cost reduction of wind and solar photovoltaic technologies. The implementation of support policies on renewable energy has been the engine that has enabled the performance of these technologies in the competitive energy market. With the analysis of the historical costs of solar photovoltaic and wind technologies, a downward trend of both technologies could be perceived and this trend is expected to be maintained in the coming years. Thus, each sector’s chain of production has an expectation of greater or lesser impact on the final cost of a given technology.